Cortical activity associated with the detection of temporal gaps in tones: a magnetoencephalography study - Mitsudo, Takako; Hironaga, Naruhito; Mori, Shuji (Frontiers in Human Neuroscience, 2014)
We used magnetoencephalography (MEG) in two experiments to investigate spatio-temporal profiles of brain responses to gaps in tones. Stimuli consisted of leading and trailing markers with gaps between the two markers of 0, 30, or 80 ms. Leading and trailing markers were 300 ms pure tones at 800 Hz or 3200 Hz. Two conditions were examined: the within-frequency (WF) condition in which the leading and trailing markers had identical frequencies, and the between-frequency (BF) condition in which they had different frequencies. Using minimum-norm estimates (MNE), we localized the source activations at the time of the peak response to the trailing markers. Results showed that MEG signals in response to 800 Hz and 3200 Hz tones were localized in different regions within the auditory cortex, indicating that the frequency pathways activated by the two markers were spatially represented. The time course of regional activity (RA) was extracted from each localized region for each condition. In Experiment 1, which used a continuous tone for the WF 0-ms stimulus, the N1m amplitude for the trailing marker in the WF condition differed depending on gap duration but not tonal frequency. In contrast, N1m amplitude in BF conditions differed depending on the frequency of the trailing marker. In Experiment 2, in which the 0-ms gap stimulus in the WF condition was made from two markers and included an amplitude reduction in the middle, the amplitude in WF and BF conditions changed depending on frequency, but not gap duration. The difference in temporal characteristics between WF and BF conditions could be observed in the regional activity.